Spotkania . niezależne pismo młodych katolików, no. 6, 1979 - ed. Zdzisław Bradel, Janusz Krupski, Józef Ruszar (s.n.], 1979)
No. 1(1977)-no. 7/8(1979), no. 17(1981)-no. 21/22(1983), no. 27/28(1984) contains contains reprints from: Paris : Editions Spotkania